2007
DOI: 10.1163/156855507782401204
|View full text |Cite
|
Sign up to set email alerts
|

Study on the microstructures of polypropylene synthesized by a novel MgCl2-supported and low Ti-loading Ziegler–Natta catalyst

Abstract: Abstract-A novel MgCl 2 -supported and low Ti-loading Ziegler-Natta (Z-N) catalyst was prepared by one-pot ball milling. Polypropylenes (PPs) with special microstructures were synthesized by using this catalyst. Complex gel-permeation chromatography (GPC) data of the resultant PPs were analyzed by fitting the molecular weight distribution (MWD) curves with multiple Flory-Schulz functions. 13 C-NMR spectra of the PPs were also analyzed. A multi-site active center model and the probable structures of the active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Stereospecific heterogeneous α-olefin polymerization has been a major research field since the first discovery of Ziegler-Natta (ZN) olefin polymerization catalysts. [1][2][3][4] Although most of the research efforts have been focused on the development of new catalytic systems for propylene polymerization, [5][6][7][8] the design and synthesis of efficient catalysts for the stereoselective polymerization of longer chain α-olefins have also attracted extensive research interests since the polymeric materials based on α-olefins could find variety of applications. Low molecular weight (MW) poly(α-olefin)s are used as base materials for lubricating oil formulation, while high MW ones are used as pour point depressant and drag-reducers.…”
Section: Introductionmentioning
confidence: 99%
“…Stereospecific heterogeneous α-olefin polymerization has been a major research field since the first discovery of Ziegler-Natta (ZN) olefin polymerization catalysts. [1][2][3][4] Although most of the research efforts have been focused on the development of new catalytic systems for propylene polymerization, [5][6][7][8] the design and synthesis of efficient catalysts for the stereoselective polymerization of longer chain α-olefins have also attracted extensive research interests since the polymeric materials based on α-olefins could find variety of applications. Low molecular weight (MW) poly(α-olefin)s are used as base materials for lubricating oil formulation, while high MW ones are used as pour point depressant and drag-reducers.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Although, Mg(OEt) 2 has a morphological subject regarding roundness and particle size distribution as compared with MgCl 2 ·nROH, the catalyst made by Mg(OEt) 2 shows a higher activity. [8,9] Industrial catalysts precursors containing magnesium compounds such as MgCl 2 or Mg(OEt) 2 in conjunction with TiCl 3 or TiCl 4 showed great performance in olefin polymerization; however, still there are lots of modifications of ZN catalysts varying in the way of preparation of the support [10][11][12][13][14] and differences in the active component compound structure and the presence of various modifying additives. [15][16][17][18] Lately, investigations have shown that doping a suitable amount of Lewis acids in MgCl 2 or Mg(OEt) 2 supports would be an effective way to improve their catalytic performance in α-olefin polymerization.…”
Section: Introductionmentioning
confidence: 99%